2007
DOI: 10.1007/s00168-007-0154-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the connections among job accessibility, employment, income, and auto ownership using structural equation modeling

Abstract: Using structural equation modeling, this study empirically examines the connections between job accessibility, workers per capita, income per capita, and autos per capita at the aggregate level with year 2000 census tract data in Sacramento County, CA. Under the specification of the conceptual model, the model implied covariance matrix exhibits a reasonably good fit to the observed covariance matrix. The direct and total effects are largely consistent with theory and/or with empirical observations across a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…We removed five outliers at a time and observed the changes in goodness-of-fit indices of the model and individual parameter estimates. Comparable to other studies (e.g., Gao et al, 2008), we found that the χ ² statistic generally increased after each step of removing outliers. This indicates a worse-fitting model since the χ ² statistic is the product of the sample size minus one (N-1) and the minimized fit function (F min ) (Byrne, 2001, p. 78;Kline, 2005, p. 135).…”
Section: Model Specification Issuessupporting
confidence: 72%
See 2 more Smart Citations
“…We removed five outliers at a time and observed the changes in goodness-of-fit indices of the model and individual parameter estimates. Comparable to other studies (e.g., Gao et al, 2008), we found that the χ ² statistic generally increased after each step of removing outliers. This indicates a worse-fitting model since the χ ² statistic is the product of the sample size minus one (N-1) and the minimized fit function (F min ) (Byrne, 2001, p. 78;Kline, 2005, p. 135).…”
Section: Model Specification Issuessupporting
confidence: 72%
“…Total effects are the sum of direct and indirect effects. Whereas other studies sometimes find opposing direct and indirect effects (e.g., Gao et al, 2008;), all variables with a direct as well as an indirect influence have synergistic effects resulting in even larger total effects. However, focusing on direct effects only would lead to inconsistent conclusions in some cases.…”
Section: Direct Indirect and Total Effectsmentioning
confidence: 63%
See 1 more Smart Citation
“…In this regard, various parking policies can be explored as a way to discourage households from purchasing a vehicle. Furthermore, improving transit services in a neighborhood can contribute to reducing car ownership as greater accessibility to jobs by transit leads to lower amount of vehicles per capita (Gao, Mokhtarian, & Johnston, 2008). In sum, multiple transport policies can be implemented as a way to reduce car ownership and support healthy walking behavior in various walkable environments.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…However, focusing on direct effects only would lead to inconsistent conclusions in some cases [26,27]. Based on the extended conditional logit choice model by incorporating mediating variable with a structural equation model, the indirect effects of socio-demographic attributes, and latent variables through mediating variable car ownership were recognized.…”
Section: As Shown Inmentioning
confidence: 99%